INTERNALISASI NILAI–NILAI BUDAYA PADA MASYARAKAT CINA BENTENG DI KAWASAN PECINAN PASAR LAMA KOTA TANGERANG - Nurahmawati, Lutfia; Martini, Martini (Edukasi IPS, 2018)
This This research purpose to: (1) the causes of the Benteng China community internalizing cultural values ​​in Chinatown, Tangerang Old Market, (2) studying the process of internalizing the cultural values ​​of Chinese people in modernization in Chinatown, Tangerang Old Market , (3) describe the interpretation of Chinese society towards the process of internalizing cultural values. This study uses a qualitative approach. The subjects of this study, namely 4 Benteng Chinese people, 2 local people, and 2 Chinese Benteng families each consisting of the first family with a father and 2 children, a second family with a father and 1 child. The focus of this reseach includes: the process of internalizing cultural values ​​in the Chinese Citadel community. The technique of data collection is done by interviews, and documentation. The method used in data analysis is data reduction, data display, and reduction of conclusions. The results showed: (1) this area is a region with unique interactions, with two different dimensions of society that are able to realize high performance, (2) the process of internalizing the Benteng Chinese cultural values ​​is carried out by an approach method supported by conducive social environment conditions and also the teacher of the parents' (Hao) devotion, (3) the interpretation of the child in the process of internalizing values live up to values ​​and actualize Chinese Fortress cultural values.